Vitrification Using Soy Lecithin and Sucrose: A New Way to Store the Sperm for the Preservation of Canine Reproductive Function - Zakošek Pipan, Maja (Animals (Basel), 2020)
SIMPLE SUMMARY: Soy lecithin and sucrose were used at different concentrations to develop and compare different vitrification methods for the cryopreservation of canine semen. All of the sperm quality characteristics were effectively preserved after devitrification when vitrification extenders containing soy lecithin at 1% and 0.25 M sucrose were used. The results suggest that vitrification is effective, fast, and simple for cryopreservation of canine semen. Furthermore, the use of soy lecithin in lieu of animal proteins (e.g., egg yolk) facilitates semen shipping to countries with strict import requirements. ABSTRACT: A challenge in freezing semen for short and long-term availability is avoiding damage to intact spermatozoa caused by the freezing process. Vitrification protocols provide better results through less manipulation of semen and shorter freezing time compared to slow freezing techniques. Our research was aimed at improving vitrification methods for canine semen. Semen quality was determined in 20 ejaculates after collection. Each ejaculate was divided into eight aliquots, each with a different extender. The control extender contained TRIS, citric acid, fructose, and antibiotics. Soy lecithin and sucrose were added to the control extender at different concentrations to make up the test extenders and final concentration of 50 × 10(6) spermatozoa/mL. From each group, a 33 µL (1.65 × 10(6) spermatozoa) suspension of spermatozoa was dropped directly into liquid nitrogen and devitrified at least one week later and evaluated as before. Soy lecithin at 1% and 0.25 M sucrose added to the base vitrification media effectively preserved all sperm qualities. Our results demonstrate the effectiveness of our methods. Vitrification media containing sucrose and soy lecithin cause a minimal decline in quality of canine semen after devitrification. Furthermore, extenders used in our research did not contain egg yolk, which was replaced by soy lecithin, thus allowing for ease of shipping to other countries with strict requirements.